Metagenomic analysis of the effects of plant- and yeast-based formulations on the grapevine leaf microbiome of cv. ‘Touriga Franca’ - Monteiro, Eliana; Baptista, Paula; Silva, Sofia; Carvalho, Márcia; Bragança, Radek; Guinan, Kieran J.; Sujeeth, Neerakkal; Cortez, Isabel; Gonçalves, Berta; Castro, Isaura (Frontiers in Plant Science, 2025)
IntroductionGrapevine is highly susceptible to fungal diseases such as downy mildew and powdery mildew, which are traditionally managed through the intensive use of chemical fungicides. However, in the context of increasingly sustainable viticulture, biofungicides derived from plant and yeast extracts are gaining attention. Despite this, their impact on the grapevine leaf microbiome, crucial for plant health and disease resilience, remains underexplored.Material and methodsThis study evaluated the effects of foliar applications of biofungicides (nettle extract, Japanese knotweed extract, and a yeast-based formulation - T66 and T90) in comparison with conventional chemical treatments and control (no treatment). Over two consecutive growing seasons, high-throughput sequencing was used to assess the diversity and composition of fungal and bacterial communities on grapevine leaves.ResultsBacterial communities were more sensitive to treatments and interannual variability than fungal communities, which remained relatively stable. Conventional treatment (CT) showed the highest influence on fungal and bacterial composition, reducing the diversity of both. Some important fungal (Aureobasidium and Sporobolomyces) and bacterial (Pseudomonas and Sphingomonas) genera associated with the promotion of plant growth, health, and biocontrol were detected.DiscussionThese findings reinforce the potential of new treatments with putative fungicide effects to modulate the leaf microbiome, particularly bacterial communities, without disrupting the natural fungal balance. Thus highlight their relevance for developing sustainable viticultural practices aimed at improving plant protection.